Myocardial Infarction with non-obstructed coronaries – atypical presentation of pheochromocytoma. (19th October 2019) - Melson, Eka; Amir, Sidra; Shepherd, Lisa; Kauser, Samina; Freestone, Bethan; Kempegowda, Punith
Abstract : Summary: Although pheochromocytoma classically presents with headaches, palpitations and paroxysmal hypertension, atypical presentations such as cardiomyopathy, stroke and subarachnoid haemorrhage have been infrequently documented. We present in this case report, an uncommon presentation of pheochromocytoma with myocardial infarction with normal coronary arteries (MINOCA). A 79-year-old woman presented with central crushing chest pain radiating to left arm associated with headache, palpitations, sweating and difficulty in breathing. For 2 years, she experienced brief episodes of headache, tinnitus, dizziness, palpitations, and sweating that spontaneously resolved. Clinical examination was unremarkable except for high blood pressure (210/105 mmHg). Her electrocardiogram showed T wave inversions from V1 to V6 and elevated troponins (774 ng/L at baseline and 932 ng/L 3 h from baseline (normal <16 ng/L) in keeping with a diagnosis of non-ST elevated myocardial infarction. Coronary angiography showed normal coronary arteries. Patient was hence treated as myocardial infarction with normal coronaries (MINOCA). Despite appropriate treatment for MINOCA, she continued to experience episodic headaches, palpitations, dizziness and erratic blood pressures (particularly severe hypertension shortly after beta-blocker administration). Further investigations revealed raised urine noradrenaline of 4724 nmol/24 h (<554 nmol/24 h) and urine adrenaline of 92863 nmol/24 h (<77 nmol/24 h). Computerised tomography demonstrated a well-defined rounded mass in right adrenal gland morphological of pheochromocytoma. She underwent laparoscopic right adrenalectomy with histology confirming pheochromocytoma. This case highlights the importance of thorough investigation for the underlying cause for MINOCA. In patients with unexplained erratic blood pressure control, pheochromocytoma should be considered as a differential diagnosis. Learning points: Pheochromocytoma is rare tumour that often presents with non-specific symptoms. It is important to investigate underlying cause of MINOCA. Thorough history is the key to diagnosis.